Research of Porous Asphalt Concrete Application on Highway Sections with The Increased Aquaplaning Danger Level - Oleksandr Rieznik; Shilin Yang; Andrii Bieliatynskyi; Meiyu Shao; Mingyang Ta (The Baltic Journal of Road and Bridge Engineering)
Statistics of road accidents show that even in the summer the number of accidents directly depends on weather conditions, and one such reason is aquaplaning in some parts of the road. Therefore, solving the issue of improving the road structure in such areas, while maintaining the regulatory strength, equality and coefficient of adhesion are relevant in road construction. The research allowed developing an improved mixture of porous asphalt mixture taking into account the physical-mechanical and operational properties. The construction of the road surface was also improved with the separation of the pavement layers, where porous asphalt mixture was used as the top layer, and the basalt canvas (impregnated) between the used construction levels was used. The mathematical calculation of the road was improved taking into account the physical phenomena occurring between the car and the road surface in the presence of water. The speed limits were calculated, and the thickness of the fluid layer was taken into account as well. The authors of the article also paid attention to the influence of road roughness on the speed limit.